Climate Extremes in the Narayani Basin of Nepal: Trends, Impacts, and Resilience Strategies - Pokharel, Navaraj; Shrestha, Pratima (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2026)
The Narayani (Gandaki) River basin—one of Nepal’s largest transboundary basins—spans diverse physiography from lowland Terai to >8,000 m Himalayan peaks with total catchment area of 46,300 km2 of which 72% is in Nepal (equivalent to around 23 percent of the country’s land area), 10% in China and 18% in India. It has over 1,500 lakes, among which over 300 are glacial lakes. Overall, there are 1279 non-glacial lakes and ponds with total area of 22,83 Km2. It is highly exposed to climate extremes (intense monsoon rainfall, floods, landslides, drought and accelerated glacier/snow melt). This paper synthesizes recent observational analyses, government data and regional assessments to characterize observed trends in temperature and hydro-meteorological extremes, document impacts on people and infrastructure, and propose priority resilience strategies for basin-scale adaptation. Key findings: (1) observed warming since the 1970s with a mean rate ≈0.03 °C yr–¹ across stations in the basin; (2) strong monsoon concentration of precipitation (≈78% of annual total) and increasing intensity of extreme rainfall events with attendant flood/landslide hazard; (3) rising cryosphere risks (glacier retreat, permafrost thaw) that amplify debris flows and sediment loads; and (4) clear opportunities for integrated resilience—improved early warning, nature-based solutions, upstream-downstream basin governance, and climate-proofed infrastructure. The paper recommended actions for scientists, planners and policymakers working in the Narayani basin.